2019
DOI: 10.1186/s13054-019-2660-x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in intensive care unit admission among pregnant and postpartum women in Canada: a nationwide population-based observational study

Abstract: BackgroundPregnancy-related critical illness results in approximately 300,000 deaths globally each year. The objective was to describe the variation in ICU admission and the contribution of patient- and hospital-based factors in ICU admission among acute care hospitals for pregnant and postpartum women in Canada.MethodsA nationwide cohort study between 2004 and 2015, comprising all pregnant or postpartum women admitted to Canadian hospitals. The primary outcome was ICU admission. Secondary outcomes were severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 46 publications
8
40
1
Order By: Relevance
“…The number of intermediate care units may have increased in France since the 2012-2013-study period, and maternal admissions in these units may be more frequent now [36]. Indications for maternal ICU admission may differ across countries, because of specific organization systems, especially billing, and ICU bed availability [13,37,38]; however, the incidence of maternal ICU admissions we found was similar as that reported in other high-resource countries [8,13,39].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The number of intermediate care units may have increased in France since the 2012-2013-study period, and maternal admissions in these units may be more frequent now [36]. Indications for maternal ICU admission may differ across countries, because of specific organization systems, especially billing, and ICU bed availability [13,37,38]; however, the incidence of maternal ICU admissions we found was similar as that reported in other high-resource countries [8,13,39].…”
Section: Discussionsupporting
confidence: 74%
“…Maternal admission to an intensive care unit (ICU) is commonly used as a single indicator of severe acute maternal morbidity [3][4][5][6][7][8]. However, maternal ICU admission depends on not only patient severity but also care organization and local practices [9][10][11][12][13]. Consequently, women admitted to the ICU could present heterogeneous levels of severity in maternal morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9]11,12,27 However, the crude hospital mortality rate in Australia (0.6%) and New Zealand (1.0%) was lower than that reported from Canada (1.3%), France (1.3%), Maryland (1.8%), the UK (1.9%), Beijing (1.9%) and the Netherlands (3.5%). [5][6][7][8][9][10][11]27 In most of these reports, a greater proportion of patients were intubated and a higher proportion of deaths were due to obstetric-related disease. It is important to recognise the different case definitions used, and that risk-adjusted mortality rates are not available.…”
Section: Main Findingsmentioning
confidence: 99%
“…7 The proximate cause of death was unable to be determined, and the ICU admission diagnosis was used to indicate disease categories associated with death. We were 103 (10) 98 (8) 133 (11) 135 (9) 137 (9) 165 (10) 178 (10) 228 (12) 254 (12) 280 (13) 1711 (11) Pre-eclampsia 105 (10) 75 (6) 102 (8) 125 (9) 141 (9) 166 (11) 157 (9) 168 (9) 199 (9) 215 (10) 1453 (9) Non-obstetric diagnoses,n (%) Respiratory 87 (8) 154 (13) 113 (9) 125 (9) 102 7105 7120 7126 7144 7123 (6) 1199 7Cardiovascular 132 (12) 118 (10) 106 (8) 106 (7) 69 (4) 74 (5) 94 5100 5108 (5) 105 (5) 1012 6Sepsis 29 331 352 (4) 60 (4) 71 (5) 74…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, TMAs could also be triggered by non-pregnancy related conditions such as thrombotic thrombocytopenic purpura (TTP), as well as pregnancy-related conditions, such as preeclampsia with severe features or eclampsia with HELLP (haemolysis, elevated liver enzymes, and low platelets) syndrome [12][13][14]. TMA is associated with adverse maternal and fetal outcomes due to the development of ESRD and ultimately leading to increased maternal mortality [15,16]. Three puerperant patients were recruited in this study with severe hemorrhage and AKI, and following renal histopathology, TMA was found to coexist with ATN.…”
Section: Discussionmentioning
confidence: 99%